2011
DOI: 10.1074/jbc.m111.259523
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Nuclear Receptor 4 (TR4) Regulates UV Light-induced Responses via Cockayne Syndrome B Protein-mediated Transcription-coupled DNA Repair

Abstract: Background: CSB, a member of the TC-NER pathway, is essential for UV light-induced DNA damage repair. Results: CSB expression is reduced in TR4-deficient tissues/cells, and restored CSB expression rescues UV hypersensitivity of TR4-deficient cells. Conclusion: TR4 modulates UV sensitivity via promoting the TC-NER DNA repair pathway through transcriptional regulation of CSB. Significance: Our findings may provide new information for the treatment of UV light-sensitive syndromes, skin cancer, and aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…In addition, the γ H2AX assay is good for quantitation of DNA rejoining, but it does not cover DNA misrepair, which also account for cell killing. However, preliminary study found that TR4 could also modulate DNA repair through the nucleotide excision repair pathway . Our results support the conclusion that TR4 might modulate the DNA repair system demonstrated by previous study, although the detail mechanism of how TR4 affects the HRR or NHEJ repair pathways still needs further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the γ H2AX assay is good for quantitation of DNA rejoining, but it does not cover DNA misrepair, which also account for cell killing. However, preliminary study found that TR4 could also modulate DNA repair through the nucleotide excision repair pathway . Our results support the conclusion that TR4 might modulate the DNA repair system demonstrated by previous study, although the detail mechanism of how TR4 affects the HRR or NHEJ repair pathways still needs further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…4 As an important transcription factor, TR4 can interact with several nuclear receptors and influence intracellular reactive oxygen species (ROS), oxidative stress resistance 5,6 and DNA damage reparation via its various down stream target genes. 7,8 In vivo studies of TR4 gene knockout mice (TR4 − / − ) demonstrated that they display impaired oxidative stress defense, 5 subfertility 9 and premature aging. 6 However, the linkage between TR4 and PCa docetaxel resistance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…TR4 also protects cells from ultraviolet radiation via regulating transcription-coupled DNA repair protein, Cockayne syndrome B [21]. Following these discoveries, the protective mechanism of TR4 in cells facing stress was further explored.…”
Section: Introductionmentioning
confidence: 99%